Implementasi Critical Path Method (CPM) Dalam Pengembangan Sistem Informasi Manajemen Kontraktor Pada PT. Sari Karya Mandiri - Yohanes LIm, Irvan; Jando, Emanuel; Siki, Yovinia Carmeneja Hoar (Utiliti Project Solution, 2025)
The development of a Contractor Management Information System is very important for the construction industry, particularly for PT. Sari Karya Mandiri, which has many permanent employees and projects that are physically completed. This research aims to develop a web-based management information system using the Critical Path Method (CPM) as a project management tool to make PT. Sari Karya Mandiri’s operations more efficient and effective. This framework is expected to address issues such as cost control, human asset management, unstructured project management, and improve project execution time efficiency. The system development method uses the waterfall model. The stages of completion include system requirements analysis, design, development, implementation, and testing. Testing is conducted to evaluate how well the system handles construction project management. The results of the research show that this framework can improve project planning, thereby reducing delays. The administrative data framework can function efficiently at PT. Sari Karya Mandiri and enhance the sustainability of the construction industry as a whole.